Nutrient cycling in agroecosystems: Balancing food and environmental objectives. Issue 7 (9th August 2017) - Tully, Kate; Ryals, Rebecca
ABSTRACT: As our rapidly growing human population puts great demands on our agricultural production systems, we must promote management practices that balance both food and environmental objectives. We focus this literature review on farm management strategies that tighten nutrient cycles and maintain yields. We examined six metrics for efficient nutrient cycling in agroecosystems: reduced runoff and erosion, reduced leaching, improved soil carbon storage, enhanced microbial biomass, low greenhouse gas emissions, improved water holding capacity, and high yields. We evaluated these metrics in six farm management practices: intercrops, agroforestry, cover crops, organic amendments, integrated crop-livestock, and conservation tillage. Agroforestry and cover crops consistently reduced runoff and erosion and improved carbon sequestration compared to conventional systems. Agroforestry was the only practice that consistently reduced nutrient leaching over conventional practices. Organic amendments and conservation tillage improve water holding capacity. There exists uncertainty in the effectiveness of these practices to reduce nitrous oxide emissions. Finally, although agroforestry tends to suppress yields, all of the practices had either a neutral or positive effect on yields. Evaluating cropping systems in terms of multiple services gives us insight into how to match practices to environmental goals, where the uncertainties lie, and where opportunities exist for improved agroecosystem management.